The linear-dependence of adhesion strength and adhesion range on temperature in soft membranes. (November 2019) - Chang, Zhenghua; Yang, Ronggui; Wei, Yujie
Abstract: The adhesion of a soft membrane plays a central role for the functionality of many biological and engineering systems, from cell adhesion to advanced materials. In this work, we demonstrated via a combination of statistical mechanics analysis and molecular dynamics (MD) simulations that the adhesion of a membrane-buffered interface could be significantly modulated due to thermally induced surface corrugations in the membrane. Not expected from classical mechanics theories, the adhesion strength is highly temperature-sensitive and reduces linearly with increasing temperature. Through statistical mechanics analysis, the dependence of adhesion on temperature is found to result from thermally induced ripples which facilitate long-range adhesion between the soft membrane like graphene sheets or lipid bilayers with the substrate. The results from MD simulations agree well with the statistical mechanics analysis. Such surprising findings may pave the way to understand temperature-sensitive kinetics in many biological systems where the interaction of cell membranes with extra-cellular environments is pivotal. Graphical abstract: Image, graphical abstract